Adhesion energy of as-grown graphene on nickel substrates via StereoDIC-based blister experiments. (November 2019) - Chang, Wei; Rajan, Sreehari; Peng, Benli; Ren, Congcong; Sutton, Michael; Li, Chen
Abstract: The interfacial interactions between as-grown graphene (G) and its metal substrates play a crucial role in large-scale graphene transfer and governing anticorrosion properties. However, few studies have been conducted on quantifying the adhesion energy of as-grown graphene, especially, in systems such as nickel/graphene (Ni/G) with strong interfacial interactions. In this study, for the first time, a novel full-field three dimensional (3D) blister test via stereo-digital image correlation (StereoDIC) was developed to characterize the interfacial interaction between as-grown graphene on nickel (Ni) and copper (Cu) substrates, respectively. To minimize effects of surface roughness and residue stress on adhesion energy, the graphene growth processes on both Cu and Ni substrates were carefully controlled to assure nearly identical growth processes in terms of temperature, growth time, heating and cooling rates. The adhesion energy of as-grown graphene on Ni was measured to be 6.775 ± 0.556 J m − 2, which is more than 7 times higher than that of as-grown graphene on Cu. Instead of van der Waals bonds, the Ni/G interface exhibited adhesion that is close to covalent bonding. We believe that this full-field 3D blister test could be further extended for evaluating strong interfacial interactions between graphene and other metal substrates. Graphical abstract: Image 1